Digital Assessment in English Language Teaching (ELT): A Systematic Literature Review - Susyla, Dian; Jaya, Sinarman (English Education Study Program Faculty of Teacher Training and Education, 2023)
The systematic literature review on digital assessment in English Language Teaching (ELT) aimed to synthesize existing knowledge, identify key themes, trends, and gaps in current research, and evaluate the effectiveness of digital assessment tools in enhancing language learning outcomes. The study adopted a systematic literature review method, involving six stages: planning, literature review, inclusion and exclusion criteria, quality assessment, data collection, and data analysis. The review found that digital assessment tools have evolved and offer opportunities for personalized learning through adaptive assessments, but also identified challenges such as technical issues, accessibility, and teacher training. The review recommended strategies for effective integration of digital assessment in ELT and implications for professional development for educators. The strategies for effective integration of digital assessment in English Language Teaching (ELT) include: leveraging online learning and digital storytelling, using automated grading systems, using automated grading systems , incorporating language learning apps and online platforms, addressing technical issues and accessibility, and providing teacher training and digital literacy support. Keywords: Digital Assessment, ELT, Systematic Literature Review